Effectiveness of a Fall Prevention Program for Elderly in Khok Kathiam Subdistrict, Mueang Lopburi District, Lopburi Province - Kritarkhom, Jantarat; Boonyoo, Arapa (Journal of health and health management, 2026)
This quasi-experimental study using a one-group pretest–posttest design aimed to examine the effectiveness of a fall prevention program among older adults. The study was conducted over a 12-week period. The sample consisted of 30 older adults selected by simple random sampling. Research instruments included a fall prevention program, a personal information questionnaire, and assessment tools for balance ability, risk of falling, fall prevention behaviors, and fear of falling. Descriptive statistics were used to analyze demographic data, and paired t-tests were employed to compare mean scores before and after the intervention. The results revealed that after participation in the program, older adults demonstrated significantly higher mean scores in balance ability (M=51.87, SD=3.23) and fall prevention behaviors (M=43.20, SD=4.23) compared with pre-intervention scores. In contrast, the mean scores for risk of falling (M=12.70, SD=3.03) and fear of falling (M=25.07, SD=6.71) were significantly lower after the intervention. The program can be applied as a health promotion strategy for older adults in other community settings.